Tinea incognito: Clinical perspectives of a new imitator - Samer Dhaher (PAGEPress Publications, 2020)
Tinea incognito is a variant of dermatophyte infection of the skin modified by an erroneously applied topical or systemic steroid. Aim of the study: to describe the various clinic-epidemiological aspects of tinea incognito found among our patients. A prospective study was carried out in the Department of Dermatology, Basra Teaching Hospital, Basra, Iraq. The clinical diagnosis was confirmed by mycological tests. Clinical data were described in more detail and the lesions were classified according to the site, shape, and extent. Ninety cases of tinea incognito were seen, median age was 34years. The initial inaccurate diagnoses were eczema in 60 patients (67%), intertrigo in 16 (18 %) and psoriasis in 14 (15%) patients. The type of topical drugs applied was topical corticosteroid (potent and fluorinated) in most cases (54.4%), fixed drug combination creams in 36.6% and a topical calcineurin inhibitor in 5.5%. Commonly presented as acute eczema-like, on hands and trunk, discoid lupus erythematosus-like lesions on the face and psoriasiform lesions on the scalp. Due to the wide range of clinical manifestations, tinea incognito imitates many skin diseases and should, therefore, be considered in any chronic, erythematous, scaly skin lesions not responding to topical treatment.